Inhibition of the mitochondrial calcium uniporter rescues dopaminergic neurons in pink1−/− zebrafish. (28th December 2016) - Soman, Smijin; Keatinge, Marcus; Moein, Mahsa; Da Costa, Marc; Mortiboys, Heather; Skupin, Alexander; Sugunan, Sreedevi; Bazala, Michal; Kuznicki, Jacek; Bandmann, Oliver
Abstract: Mutations in PTEN‐induced putative kinase 1 ( PINK1 ) are a cause of early onset Parkinson's disease (PD). Loss of PINK1 function causes dysregulation of mitochondrial calcium homeostasis, resulting in mitochondrial dysfunction and neuronal cell death. We report that both genetic and pharmacological inactivation of the mitochondrial calcium uniporter (MCU), located in the inner mitochondrial membrane, prevents dopaminergic neuronal cell loss in pink1 Y431 * mutant zebrafish ( Danio rerio ) via rescue of mitochondrial respiratory chain function. In contrast, genetic inactivation of the voltage dependent anion channel 1 (VDAC1), located in the outer mitochondrial membrane, did not rescue dopaminergic neurons in PINK1 deficient D. rerio . Subsequent gene expression studies revealed specific upregulation of the mcu regulator micu1 in pink1 Y431 * mutant zebrafish larvae and inactivation of micu1 also results in rescue of dopaminergic neurons. The functional consequences of PINK1 deficiency and modified MCU activity were confirmed using a dynamic in silico model of Ca 2+ triggered mitochondrial activity. Our data suggest modulation of MCU‐mediated mitochondrial calcium homeostasis as a possible neuroprotective strategy in PINK1 mutant PD. Abstract : In a pink1 −/− zebrafish model of Parkinson's disease, both genetic and pharmacological inhibition of the mitochondrial calcium uniporter (MCU) rescue dopaminergic neurons via normalisation of mitochondrial complex I activity. In contrast, genetic inactivation of the voltage‐dependent anion channel 1 (VDAC1) did not rescue dopaminergic neurons.